Bioavailability of iron, zinc, and provitamin A carotenoids in biofortified staple crops - La Frano, Michael R.; De Moura, Fabiana F.; Boy, Erick; Lönnerdal, Bo; Burri, Betty J. (Oxford University Press, 2014)
International research efforts, including those funded by HarvestPlus, a Challenge Program of the Consultative Group on International Agricultural Research (CGIAR), are focusing on conventional plant breeding to biofortify staple crops such as maize, rice, cassava, beans, wheat, sweet potatoes, and pearl millet to increase the concentrations of micronutrients that are commonly deficient in specific population groups of developing countries. The bioavailability of micronutrients in unfortified staple crops in developing regions is typically low, which raises questions about the efficacy of these crops to improve population micronutrient status. This review of recent studies of biofortified crops aims to assess the micronutrient bioavailability of biofortified staple crops in order to derive lessons that may help direct plant breeding and to infer the potential efficacy of food-based nutrition interventions. Although reducing the amounts of antinutrients and the conduction of food processing generally increases the bioavailability of micronutrients, antinutrients still possess important benefits, and food processing results in micronutrient loss. In general, biofortified foods with relatively higher micronutrient density have higher total absorption rates than nonbiofortified varieties. Thus, evidence supports the focus on efforts to breed plants with increased micronutrient concentrations in order to decrease the influence of inhibitors and to offset losses from processing.